Operasional dan pemeliharaan jaringan irigasi subak di Kabupaten Tabanan - - Sumiyati; I Wayan Windia; I Wayan Tika (Jurnal Kajian Bali (Journal of Bali Studies), 2017)
This research was conducted in order to understand the operational and maintenance of irrigation network in traditional Balinese irrigation system of subak in Tabanan regency. It spesific aim is to develop a documentation which is useful as reference about operational and maintenance of irrigation network in subak system. The sample of this research are four subak in Tabanan regency which are subak in the upstream, middle, and downstream areas, including Subak Bunyuh, Subak Sigaran, Subak Guama, and Subak Sungsang. The research was conducted by survey and depth interview methods. The operational and maintenance of irrigation networks in subak system in Tabanan regency includes matelik (monitoring channel), nyilih yeh (borrow the water), magilihan (rotation of water irigation), kempelan (maintenance of traditional weir), ngeduk nyanyad (draining mud), nabdab yeh (arrangement of water irrigation distribution), metpet munduk (lining stabilitation.), and ngampad (chanel clearing). This article concludes that all subak samples in Tabanan regency carry out operational and maintenance activities the irrigation networks in the subak system.